Status, practices and problems of selected teacher-advisers on school paper management in Manila and provincial public high schools a study - Querubin, Iluminada Reyes 1924-
The purpose of the study is to pinpoint the status, practices and problems of selected teacher-advisers on school paper management of public Manila and Provincial high schools with a view of making the school paper a more effective laboratory for responsible newspaper work. The findings indicate that only a small portion of the respondent teacher-advisers have had formal training in journalism, thus, there is a need to implement a high school journalism program.